PROFIT TAX IN UZBEKISTAN - Zaripov Khusan Bakhodirovich (American Journals, 2023)
This article talks about the tax, which is one of the forms of manifestation of additional products and the main source of the state budget revenue, that the improvement of the budget and tax system in Uzbekistan is one of the central issues of economic reforms and state economic policy, the simplification of the country’s tax system and profit tax. described the procedure for its use. Also, the tax system of Uzbekistan is analyzed, and the opinions of foreign and local scientists are presented in the article.
Keywords: tax, tax system, profit tax, budget, tax policy, tax benefits, taxation, tax burden.